Is "Working Together" Working? An Investigation Into Tertiary Students’ Attitudes Toward Collaborative Assessments - Scherman, R (Interprofessional Health Studies, Auckland University of Technology, 2014)
A growing body of knowledge is calling for a new pedagogic discourse in tertiary eduation that draws on the importance of peer learning and collaborative assessment as a meaningful framework for interdisciplinary studies. The literature highlights the benefits to students of cooperation and collaboration in the classroom, and some research even describes team-based testing and other shared-learning assessment structures. The literature also describes collaborative assessment strategies for academics. However, what seems to be lacking is a better understanding of the students’ own perspectives on the idea of collaborative assessments, where students “share” grades. With that in mind, and with the growing emphasis on interprofessional practice at AUT, I wanted to know what students thought of the idea of shared-learning environments and collaborative assessments. In particular, my aim was to assess whether or not those attitudes were influenced by either the students’ worldviews (i.e. individualism or collectivism) or their perceptions of academic achievement (i.e. belief that they were obtaining D, C, B or A range grades). A group of 82 AUT undergaduate students taking Social Psychology (a paper without a pre-req that attracts a large number of multi-disciplinary and ethnically-diverse students from across two Faculties) completed a purpose-built 10-question survey (with six additional demographic questions). (NOTE: AUTEC approval was obtained for the study.) Preliminary analyses indicate that a stronger sense of collectivism positively correlates with more positive attitudes toward collaborative assessments. On the other hand, perceiving themselves to be getting higher grades appears to be negatively correlating with positive attitudes toward collaborative assessments. A full discussion of the descriptive data will be offered at the presentation, in addition to the inferential analyses (still ongoing) and their implications for lecturers and interprofessional pedagogy.